N, S self‐doped porous carbon with enlarged interlayer distance as anode for high performance sodium ion batteries. (21st December 2020) - Li, Qun; Zhang, Ya‐Nan; Feng, Shuai; Liu, Di; Wang, Guixiang; Tan, Qinglong; Jiang, Shuting; Yuan, Jianjun
Summary: To enhance the cycling ability and rate property of carbon anode material for sodium ion battery, an easy, green, and scalable thermal pyrolysis method had been exploited to synthesize the nitrogen, sulfur self‐doped porous carbon anode derived from the walnut shell. The microstructure and electrochemical properties of this synthesized porous carbon materials are investigated by tuning the thermal pyrolysis temperature. When it is at 1000 °C, the porous carbon material exhibits the largest average interlayer distance of about 0.408 nm (d002 ) and excellent electrochemical performance. The porous carbon electrode material carbonized at 1000°C for sodium ion battery manifests a high reversible specific capacity of about 305 mAh g −1 at a current density of 100 mA g −1 after 200 cycles, and as large as 182 mAh g −1 at 1 A g −1 after 1500 charge/discharge cycles. Nitrogen and sulfur doped biomass carbon anode material with an excellent storage capacity for sodium ion, makes it an appealing candidate as cheap and high‐performance anode materials for sodium ion batteries. Abstract : N, S self‐doped carbon derived from walnut shell was prepared by an easy, green, and scalable pyrolysis method. Outstanding sodium ion storage performance was obtained due to enlarged interlayer distance and high pseudocapacitive contribution. The N, S self‐doped carbon electrode demonstrates high specific capacity, good rate performance, and long‐term cycling life.